Economic evaluation of pumped storage power station based on multi-scenario stochastic Commitment Model. Issue 1 (December 2020) - Wang, Xiaohui; Lu, Yanchao; Zhou, Bo
Abstract: Pumped storage power stations have excellent characteristics such as fast start and stop speed, rapid load increase and decrease speed, and low forced outage rate, which can effectively improve the safety and economy of the power grid. This paper proposes a method for economic analysis of pumped storage based on a multi-scenario random unit combination model. In this paper, we build a scenario tree model based on the statistical characteristics of wind power and load forecast errors, and use a scenario modeling method based on associated nodes to build a stochastic unit combination model; Based on the results of system analysis, the economic efficiency of pumped storage power station is calculated, and the feasibility of the model is verified by example analysis, and the difference between calculation results of different models is also analyzed.